Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean - Last, Peter R.; Yearsley, Gordon K.; Motomura, Hiroyuki (Zootaxa, 2005)
A new scorpionfish, Lioscorpius trifasciatus sp. nov., is described from material collected from the eastern Australian continental slope between Hinchinbrook Island (central Queensland) and Port Jackson (New South Wales) in 250–400 m depth. It differs from the only other member of the genus, the widely distributed Indo–West Pacific congener, L. longiceps Günther, in having the following combination of characters: 3 anal-fin spines (rather than 2), smaller head dimensions (i.e. length 38.7–42.3% SL, orbit 7.4–8.2% SL, upper jaw 19.1–20.7% SL, and maxilla depth 5.3–6.1% SL), shorter predorsal distance (36.2–38.8% SL), some relatively long fin elements (i.e. longest pelvic-fin ray 18.6–19.8% SL, first anal-fin spine 5.0–6.6% SL, and second anal-fin spine 10.4–12.7% SL), 3 diagonal red bands across the pectoral fin, and a red caudal-fin margin.